Endotrophin, a fibroblast matrikine, may be a driver of fibroblast activation in fibro-inflammatory diseases - Reese-Petersen, Alexander L.; Genovese, Federica; Zhao, Lei; Banks, Glen; Gordon, David A.; Karsdal, Morten A. (Frontiers in Molecular Biosciences, 2023)
Perspective article